Epifaunal Habitat Associations on Mixed and Hard Bottom Substrates in Coastal Waters of Northern Norway - Dunlop, Katherine; Harendza, Astrid; Plassen, Liv; Keeley, Nigel (Frontiers in Marine Science, 2020)
Hard and mixed seafloor substrates are an important benthic habitat in coastal northern Norway and they are known to be colonized by relatively diverse communities of sessile epifauna. These assemblages are highly susceptible to physical damage and stresses imposed by organic material from industrial and municipal sources. However, despite increasing prevalence of stressors, the diversity and distribution of benthic substrates and biological communities in coastal Arctic and sub-Arctic regions remain poorly documented. In response, this study has characterized the composition of mixed and hard bottom substrates and associated sessile epifauna in fjords in Finnmark, northern Norway, using remote sensing and an innovation low-cost towed camera method. The study fjords supported a dense covering (0.1 to 0.68 individuals m-2) of sponge taxa common to deep-water ostur sponge habitats (Geodia sp., Mycale lingua, Polymastia sp., Phakellia ventilabrum and Axinella infundibuliformis). In addition, aggregations of the soft coral (Duva florida), the tunicate (Ascidia sp.), the seastar (Ceramaster granularis) and anemone (Hormathia digitata) were prominent fauna. The small-scale spatial patterns of the epifaunal communities in this study were primarily influenced by the local hydrodynamic regime, depth, the topographical slope and the presence of hard bedrock substrates. This description of the composition, distribution and the identification of drivers of the distribution of epibenthic communities is valuable for the development of predictive habitat models to manage the benthic impact of multiple stressor on these ecological valuable and vulnerable Arctic habitats.